PERCEIVED AND OBSERVED TEACHING CREATIVITY OF ENGLISH TEACHERS IN SMKN 1 NEGARA - Mahayana, Dwi Hendra; Artini, Luh Putu; Padmadewi, Ni Nyoman (International Journal of Language and Literature, 2020)
Teachers’ creativity is an important aspect that has an influential effect on students’ competence, however research on this particular topic is hardly found. This study aimed at investigating teachers’ creativity from two perspectives: From how they perceived and what they implemented in the classroom, and then to describe the discrepancy between the two Embedded mixed method was used as the design of this study which means the qualitative data was dominant than quantitative data QUAL (quan). Two EFL teachers of SMKN 1 Negara were chosen as the subject. Self-rated questionnaire, classroom observation sheet, and in-depth interview were used as the instruments. The discrepancy of two data were occurred. The investigation proves that the teachers rarely teach based on the lesson plan, teach inductively, conduct innovative learning by using technology as learning media. The teachers mainly focused on using same media in several meetings, conduct monotonous teaching activity.